Profile of Positive Cultures in Pediatric Intensive Care Unit: A Retrospective Cohort Study - Isha Bhagat; Rekha Solomon; Dhruv Mamtora; Garima Mehta; Lakshmi Shobhavat (Pediatric Infectious Disease)
Infections are an important cause of morbidity and mortality in the pediatric intensive care unit (PICU). Aims and objectives: To study the demographic profile, describe the spectrum and resistance pattern of organisms isolated from blood and respiratory cultures, and study the outcome. Materials and methods: This retrospective observational study, conducted from January 1 to December 31, 2021, was performed on children with positive blood and respiratory cultures admitted to the PICU of a tertiary care multispecialty hospital. Demographic profile and outcome measures were recorded. Positive cultures and resistance patterns were noted. Results: There were 139 children with positive cultures, with a median age of 12 months. The majority of children had comorbidities (62.6%), previous hospital admissions (83.5%), and/or antibiotic exposure (85.4%). Gram-negative bacilli (GNB) comprised 99% of positive respiratory cultures in hospital-acquired infections (HAI), and the most common organisms grown were Acinetobacter species, Klebsiella species, and Pseudomonas species. On antibiotic sensitivity testing, approximately three-fourths of the organisms showed multidrug resistance. High levels of carbapenem resistance were seen in isolates of Acinetobacter baumannii (40/48), Klebsiella pneumoniae (25/29), and Pseudomonas aeruginosa (22/37). Out of the 139 patients included in the study, 86 (61.9%) survived. On multivariate analysis, multidrug resistant organisms (MDRO) were significantly associated with mortality (p = 0.02). Conclusion: Infections in critically ill children were predominantly due to gram-negative organisms. There is a trend toward increasing antibiotic resistance over time. Infection with MDRO is associated with mortality. Highlights: Infections represent a major burden in developing countries, especially in critically ill children. Our study shows high levels of multidrug resistance and increasing carbapenem resistance over time. We have demonstrated a higher risk of mortality in children with MDRO.